Occurrence of insecticide resistance in field populations of Chrysoperla zastrowi arabica (Neuroptera:Chrysopidae) in India - Venkatesan, T; Jalali, S K; Murthy, K S; Rabindra, R J; Lalitha, Y (The Indian Journal of Agricultural Sciences, 2011)
The green lacewing (Chrysoperla zastrowi arabica Henry et al.) was evaluated during 2006–08 using the bioassay technique developed by IOBC/WPRS Working Group. Based on the mortality response with different field populations to the field recommended dosage of monocrotophos (ppm), different concentrations, viz 1 728.00, 864.00, 432.00, 216.00, 108.00, 54.00, 27.00, 13.50, 6.75, 3.38 and 1.69 ppm were tested against five days old larvae of C. zastrowi arabica under laboratory conditions. Twenty-four hour bio-assay studies revealed that there was variation among different populations. The population collected from Sriganganagar had highest resistance (1819.72 ppm), followed by Delhi (1 564.05 ppm). Populations collected from lab reared and Shimla was highly susceptible to monocrotophos with LC50 of 4.02 ppm and 5.86 ppm, respectively. Of the 9 field populations, Sriganganagar population exhibited 452.66 folds resistance compared to laboratory population, however, Shimla was found to be most susceptible (1.46 fold resistance). The study revealed the occurrence of insecticide resistance to monocrotophos in field populations of C. zastrowi arabica for the first time in India.